MRONJ and ORNJ: When a single letter leads to substantial differences. (November 2020) - Terenzi, Valentina; Della Monaca, Marco; Raponi, Ingrid; Battisti, Andrea; Priore, Paolo; Barbera, Giorgio; Romeo, Umberto; Polimeni, Antonella; Valentini, Valentino
Highlights: Differences are related to different pathogenesis process and time of occurrence. Patients with MRONJ are much more "complicated". We can consider ORNJ as a "localized" disease and MRONJ as a "diffused" one. For us, microvascular recosntruction is indicatedi in advanced stages ORNJ.